2014
DOI: 10.1186/1471-2458-14-252
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health communication and awareness of contraceptive methods among secondary school female students, northern Ethiopia: a cross-sectional study

Abstract: BackgroundAdolescent girls continue to fall victim to unintended pregnancy and its consequences, with particular problems arising in low income countries. Awareness about methods of contraception is an important step towards gaining access and using suitable contraceptive methods. However, studies assessing the relationship between sexual and reproductive health communication and awareness of contraceptive methods among secondary school female students are lacking.MethodsA cross sectional study was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 19 publications
5
59
4
1
Order By: Relevance
“…This could be due to open talk with their parents, they would have a good understanding and knowledge about SRH services and this can encourage them to use the service. This finding was agreed with other studies done in Mekele town which brought a positive finding sexual and reproductive health communication as a means of contraceptive awareness [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This could be due to open talk with their parents, they would have a good understanding and knowledge about SRH services and this can encourage them to use the service. This finding was agreed with other studies done in Mekele town which brought a positive finding sexual and reproductive health communication as a means of contraceptive awareness [20].…”
Section: Discussionsupporting
confidence: 92%
“…This could be in fact because of the fear of unwanted pregnancy females need to use at least contraceptive. This judgment was supported by a study conducted in Awabe district, were those respondents who ever had sexual intercourse 1.88 times more likely to utilize the service than those who were not sexually active [20].…”
Section: Discussionmentioning
confidence: 88%
“…Sexual and reproductive health issues = in this study includes STI/HIV/AIDS, Contraceptive, Menstruation, unwanted pregnancy, premarital sex, Sexual intercourse, physical and psychological changes during puberty [38].…”
Section: Operational Definitionmentioning
confidence: 99%
“…There is however no scientific evidence to back this claim. Studies have rather shown that adolescents are better able to make informed decisions about their reproductive health [11] and have better reproductive health outcomes when provided with the necessary education, information, and services [9, 12]. …”
Section: Discussion and Recommendationmentioning
confidence: 99%